2009
DOI: 10.3748/wjg.15.2293
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of adalimumab for treating fistulizing Crohn's disease with pyoderma gangrenosum: Two birds with one stone

Abstract: Crohn's disease (CD) is a chronic relapsing and remitting autoinflammatory disorder of the gastrointestinal tract that has many intestinal and extraintestinal complications. The purpose of treatment is long-term remission, reduction of complications, and improvement of patients' quality of life. In many cases, this can be quite challenging and it is necessary to have a well thought out management strategy. We present the case of a 38-year-old woman with fistulizing CD that manifested as diffuse abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 10 publications
0
27
0
3
Order By: Relevance
“…4,[17][18][19][20] A small (N ¼ 30) randomized controlled trial comparing infliximab to placebo for the treatment of pyoderma gangrenosum found a higher rate of clinical improvement at week 2 in the infliximab recipients (46% versus 6%, P ¼ 0.025), 21 although not all of the patients in this series had inflammatory bowel disease. A recent publication of an observational analysis of adalimumab use for CD in a referral center 22 found a meaningful rate of complete resolution of EIMs at week 4 (31.5%) and week 12 (41%).…”
Section: Discussionmentioning
confidence: 99%
“…4,[17][18][19][20] A small (N ¼ 30) randomized controlled trial comparing infliximab to placebo for the treatment of pyoderma gangrenosum found a higher rate of clinical improvement at week 2 in the infliximab recipients (46% versus 6%, P ¼ 0.025), 21 although not all of the patients in this series had inflammatory bowel disease. A recent publication of an observational analysis of adalimumab use for CD in a referral center 22 found a meaningful rate of complete resolution of EIMs at week 4 (31.5%) and week 12 (41%).…”
Section: Discussionmentioning
confidence: 99%
“…Limited data about the efficacy of ADA on EIM resolution have been previously reported (21,26,27). CARE study was the largest published study assessing the efficacy of ADA on EIM resolution with near one thousand patients included (21).…”
Section: Continous Variables Mean ± Sd Mean (Sd) P (T < T)mentioning
confidence: 99%
“…Se inicia con manejo local con protectores de la piel que faciliten la adherencia de las prótesis a la piel afectada, debiendo agregar corticoides sistémicos e inmunosupresores en casos más graves para lograr el control de la enfermedad 8 . En la fase de mantención destacan los antagonistas del factor de necrosis tumoral, que a pesar de los costos están indicados en casos refractarios al tratamiento habitual, además de ser efectivos contra la enfermedad de base 9 . Sin embargo, se han descrito casos de PG periileostómico que se presentan durante el tratamiento con infliximab 10 .…”
Section: Discussionunclassified